70 The effect of ethnicity on left ventricular adaptation to exercise. (June 2018) - Basu, Joyee; Finocchiaro, Gherardo; Malhotra, Aneil; Parry-Williams, Gemma; Miles, Chris; Tome, Maite; Sharma, Sanjay; Papadakis, Michael
Abstract : Background: Ethnicity has emerged as a major determinant of cardiac adaptation to exercise with black athletes (BAs) exhibiting greater LV wall thickness compared with white athletes (WAs). Left ventricular (LV) geometry using relative wall thickness (RWT) and LV mass index (LVMI) has been proposed as a more accurate tool in differentiating between physiological and pathological left ventricular hypertrophy in athletes, compared to absolute LV wall thickness and cavity size. Studies have characterised LV geometry in WAs but there is a paucity of data in BAs. Purpose: To assess the effect of black ethnicity on LV geometry in healthy male and female athletes. Methods: A total of 512 male (mean age 21.9±4.9 years) and 128 female (mean age 21.1±4.7 years) BAs and 644 male (mean age 22.1±5.4 years) and 439 female (mean age 21.3±4.8 years) WAs underwent pre participation screening with an electrocardiogram and echocardiogram. Athletes participated in a variety of sporting disciplines with static (1% BAs vs 9% WAs), dynamic (63% BAs vs 28% WAs) and mixed (33% BAs vs 62% WAs) components. LV geometry was classified into 4 groups: normal (low LVMI/low RWT), concentric remodelling (low LVMI/increased RWT), eccentric hypertrophy (increased LVMI/low RWT) and concentric hypertrophy (increased LVM/increased RWT). Results: Male BAs exhibited an increased RWT (0.37±0.07 vs 0.36±0.06; p=0.008) and LVMI (104.6±24 g/m 2 vs 82.1±16.7 g/m 2 ; p<0.001) compared to female BAs. Male BAs demonstrated significantly higher RWT (0.37±0.07 vs 0.36±0.05; p=0.005) and LWMI (104.6±24 g/m 2 vs 101±21 g/m 2 ; p=0.02) than male WAs. In contrast female BAs exhibited similar RWT (0.36±0.06 vs 0.35±0.05; p=0.06) and LWMI (82.1±16.7 g/m 2 vs 83±17 g/m 2 ; p=0.56) to female WAs. Concentric remodelling or hypertrophy was present in 20% of male BAs and 13% of male WAs (p<0.001) but only 8.5% and 7% in female BAs and WAs (p=0.71), respectively (Figure 1). The upper limit of RWT defined as 2 SD above the mean was 0.51 in male BAs, 0.45 in male WAs, 0.45 in female BAs and 0.43 in female WAs (Figure 1). In a multivariate model which included age, gender, ethnicity and sporting discipline, black ethnicity was the only predictor of concentric remodelling or hypertrophy (OR 1.9, 95% CI 1.5 to 2.6, p<0.001). Conclusion: Male BAs exhibit significantly higher RWT and LMVI than WAs with 20% demonstrating concentric remodelling or hypertrophy. Such phenotypes have important implications as they overlap with hypertrophic cardiomyopathy.